BathyGlobe GapFiller: A planning tool to help fill the gaps in world bathymetry - Ware, Colin; Mayer, Larry; Johnson, Paul (The International Hydrographic Review, 2025)
To efficiently map the oceans in support of the SeaBed 2030 project and other mapping programs, newly collected mapping lines should ideally not duplicate existing data but slightly overlap prior mapping coverage. BathyGlobe GapFiller is a software tool designed to support planning for transit and area mapping. At its core is an algorithm that adjusts transit lines so that they overlap existing lines by a specified amount. Two novel methods for accomplishing this are presented. The better solution uses a custom overlap detecting filter. While it is more computationally intensive than the alternative, it performs better and is robust. Other capabilities of the BathyGlobe GapFiller are described, including swath width estimation based on system specifications and/or past performance, automatic transit planning, polygon filling, and the production of detailed statistics representing planned survey coverage, overlap and time to complete the survey.